Illiteracy Factor of Medical Resume Sheets in Hospital X: Faktor Ketidakterbacaan Lembar Resume Medis Di Rumah Sakit X - Hermawan, Nabilla Aurellia Putri; Alifia, Nayla Fauziah; Yulianita, Novi Eka; Khasanah, Maulidya; Sakinah, Mulazimatus; Sutha, Diah Wijayanti (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
The readability of a medical resume is an indicator of the quality of medical records. Factors that caused illiteracy included the doctors’ habit of writing diagnoses in a hurry, no policies or procedures that regulate the use of capital letters and uneven typewriting.This type of research is Field Research, with qualitative descriptive methods. Data from observations, interviews, field research observations, and study findings from medical records are all processed. Based on the conclusion that the researchers took there are 3M namely Man, Methode, and Money. Man Factor: Physicians continue to be uncooperative with Health Energy, and they show little regard for the accuracy of the diagnostic files in medical records.Factor Method does not adhere to Operational Standard Procedures (SOP) on readability or proper writing on medical resumes, nor do they provide uniform guidelines for the usage of writing and abbreviations in resumes. The lack of incentives and penalties for healthcare providers, known as the Money Factor, has led to a lack of literacy in medical resumes.